2018
DOI: 10.1186/s12883-018-1073-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary headaches in children and adolescents – experiences at a single headache center in Korea

Abstract: BackgroundHeadache is a common complaint in children and adolescents. Recently, an increased prevalence of headache in children and adolescents has been reported.MethodsWe retrospectively reviewed the medical records of children and adolescents attending the Headache Clinic of Daejeon St. Mary’s Hospital during the period from January 2005 through December 2016.ResultsThe study population consisted of 2466 children, aged between 3 and 18 years (mean age: 10.9). Our study showed an increase in the number of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
4
19
0
1
Order By: Relevance
“…Our results reported that migraine was the most prevalent (10.9%), followed by TTH (6.2%) and chronic headache (0.9%). Similarly to our study, a population study consisting of 2,466 children, aged between 3 and 18 years and which included 60% females and 40% males, showed that migraine was the most prevalent headache followed by TTH, and then other primary headaches (22). Our results are also in line with the Indian study that showed that migraine was most prevalent in their cohort followed by TTH (18).…”
Section: Discussionsupporting
confidence: 81%
“…Our results reported that migraine was the most prevalent (10.9%), followed by TTH (6.2%) and chronic headache (0.9%). Similarly to our study, a population study consisting of 2,466 children, aged between 3 and 18 years and which included 60% females and 40% males, showed that migraine was the most prevalent headache followed by TTH, and then other primary headaches (22). Our results are also in line with the Indian study that showed that migraine was most prevalent in their cohort followed by TTH (18).…”
Section: Discussionsupporting
confidence: 81%
“…Headache may result in significant disability, including missed school days, and extra-curricular activities, decrease participation in regular activities, and loss of productivity [18]. Previous population-based studies reported that students missed on average 7.2 school days in the last 6 months due to migraine, which is comparable to our study where the mean was 0.99 days in the last month [19].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, this group might be a particularly fruitful target for intervention development. Further, children with migraine are likely to have a parent with migraine 23,24 ; therefore, a pediatric headache treatment clinic could be an advantageous setting in which to develop these intervention strategies.…”
Section: Discussionmentioning
confidence: 99%